Diagnóstico e manejo integrado de pragas (MIP) na coleção de fungos do herbário João Murça Pires (MG) - SOUZA, Carla Vitória Lobo de (2019)
This work aims to understand the importance of Preventive Conservation in combating pests in biological collections within the framework of science museums.The object of study was the collection of fungi from Herbarium João Murça Pires (MG), from the Museu Paraense Emílio Goeldi, an important reference for Amazonia that preserves specimens of organic composition that can become a target for pests. In order to preserve it through its importance, the main objective was to develop a proposal for Integrated Pest Management (IPM) for the Collection. In order to achieve this, the methodology was divided into three fronts: the first one consisted in the analysis of the space and conservation practices used, the second in the analysis of the macroclimate (use of the datalogger model HT-70) and the third in the identification of pests (with the aid of a magnifying glass, in partnership with entomologists ). With the obtained data, it was verified that the maintenance of the herbarium, as far as possible, includes actions that help in the fight against this biological agent as the ban of food, the regulation of the climatization (Temperature between 21º to 30º C and RU to 35% ), cleaning (even if superficially) and the use of poisoning (by phosphine gas). However, due to other problems such as the presence of vegetation around and the non-fence of doors, windows and cabinets, there is still possibility the entrance of pests in the collection, being found during this study a total of 25 insects divided between the orders Blattodea, Coleoptera, Diptera, Ephemeroptera and Hymenoptera. Therefore, in order to take measures that are effective in combating pests and beneficial to both the collection and the professionals working in it (avoiding the use of phosphine gas, which is highly toxic to humans), we propose an Integrated Management of Pests (IMP) with proposals and suggestions against the entry and permanence of pests in the collection. This study highlights the importance of preventive conservation in mycological collections, guaranteeing the integrity of specimens that can support several types of studies with significant contributions to science.